Analisis tingkat berpikir mahasiswa berdasarkan teori Van Hiele ditinjau dari gaya kognitif - Alpha Galih Adirakasiwi; Attin Warmi (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2018)
theory in three dimension at kapita selekta geometry subject, students who have cognitive style field independent (FI), Filed Intermediate (FDI) and Field dependent (FD). This research is descriptive by qualitative approach. Research subject are four students of third semester B that consists of one student refers to cognitive field independent, two students refers to cognitive field intermediate and one students refers to cognitive field dependent. Instrument of this research is GEFT (Group Embedded Figure Test), geometry test and interview guideline. Data collection is carried out by giving test and interview. The result if research shows that (a) the subject that includes to cognitive field independent (FI) it is in fourth level (accuracy), (b) the subject that includes to cognitive field dependent (FD) it is in third level (deducation) and (c) the subject that includes to cognitive field intermediate (FDI-1) it is in fourth level accuracy that hasn’t completed and the subject that includes to cognitive field intermediate (FDI-2) it is in third level deducation Keywords: Teori van Hiele, Cognitive Style, Geometry